Komodo National Park fiber optic network design and analysis by considering earthquake epicenter - Darmawan, Muhammad Riza; Aini, Nurul; Admaja , Awangga Febian Surya; Apriono, Catur (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2021)
Labuan Bajo and Komodo National Park (KNP) are the government's agendas in the tourism sector by making the area a premium tourist destination. On that basis, the tourism potential of the region requires infrastructure development to support this plan. One of the critical infrastructures is telecommunications, where the region does not have a direct fiber-optic line. In this paper, the authors propose two scenarios design of fiber-optic networks that also consider the potential for an upward fault earthquake in the northern waters of Labuan Bajo and KNP. The design is analyzed using calculation results of the power link budget, rise time, bit error rate (BER), and Signal to Noise Ratio. The BER value obtained is 5.63 x 10-13, which is still below the parameter threshold of 10-12 with a design that avoids the epicenter of the disaster and a longer route. The SNR value on the longest route (route 7) is 34.69 dB. The SNR value has met the SNR standard, which is 21.5 dB.